... And the Computer Plays Along: Software can improvise on the spot to accompany the performance of live musicians. - Shein, Esther (Communications of the ACM, 2023)
The article reports on artificial intelligence (AI) that can improvise to accompany live music performances. Topics include a concert held at the Massachusetts Institute of Technology (MIT) that utilized this technology and the development of such software in 1987 by musician and composer George Lewis.